Santri Students’ Satisfaction with E-Learning in Advanced-Level Listening Courses - Qiftiyah, Nor; Suryanto, Bradiansyah Tri (English Language Teaching Journal, 2025)
This study aims to explore students’ satisfaction levels and the factors influencing their satisfaction with the use of e-learning in Listening courses at Nurul Jadid University, particularly for advanced students. A mixed-methods approach was employed, collecting data through a Likert-scale questionnaire and Focus Group Discussions (FGDs) involving 32 students. The questionnaire results showed that the majority of respondents (65.6%) were satisfied with e-learning, indicating increased learning motivation. FGDs revealed that ease of access, quality and relevance of materials, interactivity, and lecturer support were key factors contributing to student satisfaction. Students also emphasized the importance of stable internet access and user-friendly platform design to optimize the learning experience. These findings align with previous research demonstrating that e-learning can enhance student engagement, motivation, and participation. The study concludes that e-learning effectively supports listening skill development for advanced learners. Educational institutions are recommended to continuously improve e-learning platforms by involving students in the development process, providing high-quality interactive materials, and ensuring technical and pedagogical support. This research contributes to developing more effective and responsive e-learning environments, particularly in advanced-level language courses.